Bisphenol A attenuates thyroxine‐induced apoptosis in ovarian granulosa cells of pigs. Issue 6 (29th April 2019) - Song, Dan; Wu, Guoyun; Wei, Quanwei; Shi, Fangxiong
Contents: Bisphenol A (BPA) is a chemical of high production volume that is used widely in many industries and is known as a xenooestrogen and anti‐thyroid hormone endocrine disrupter. There is little information regarding the effects of BPA in the presence of thyroid hormone on porcine granulosa cell development. Thus, the primary granulosa cells were treated with thyroxine (T4, 10 nM), BPA (10 µM) or T4 plus BPA; we subsequently evaluated the effects of T4 or BPA on 17β‐estradiol synthesis, cellular proliferation and apoptosis. Our data showed that BPA significantly increased the accumulation of 17β‐estradiol and promoted granulosa cell proliferation, whereas T4 significantly decreased 17β‐estradiol and had no effect on cellular proliferation. In addition, it was noteworthy that T4 treatment induced apoptosis in porcine granulosa cells and BPA co‐incubation attenuated T4‐induced apoptosis as shown from flow cytometric assay analysis. We hypothesized that BPA attenuates T4‐induced apoptosis by regulating 17β‐estradiol accumulation and oestrogen receptor‐mediated signalling pathways. In conclusion, our results demonstrated that T4 affected 17β‐estradiol accumulation and induced cellular apoptosis, but did not affect granulosa cell proliferation. Exposure to BPA increased 17β‐estradiol accumulation, promoted granulosa cell proliferation and attenuated T4‐induced apoptosis in porcine granulosa cells in vitro.